Anti‐tumour necrosis factor treatment increases circulating T helper type 17 cells similarly in different types of inflammatory arthritis. (23rd June 2015) - Hull, D. N.; Williams, R. O.; Pathan, E.; Alzabin, S.; Abraham, S.; Taylor, P. C.
Summary We investigated changes in circulating T helper type 17 (Th17) cells following anti‐tumour necrosis factor (TNF) in rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) patients. Peripheral blood mononuclear cells (PBMC) were isolated from 25 RA, 15 AS and eight PsA patients at baseline 4 and 12 weeks after treatment, and Th17 cell frequencies were analysed using interleukin (IL)‐17 enzyme‐linked immunospot (ELISPOT) and flow cytometry. A significant increase in IL‐17‐producing cells was observed by ELISPOT in RA and AS patients at 12 weeks. Flow cytometry confirmed significant increases in CD4+IL‐17+ cells at 12 weeks in RA and AS and 4 weeks in PsA patients. Anti‐TNF treatment increases circulating Th17 cells in three different diseases.